2022
DOI: 10.2147/ott.s378933
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Galectin-9 are Increased in Cervical Cancer Patients and are Higher in Advanced Clinical Stages

Abstract: Purpose Cervical cancer (CC) is the second most frequent cancer in undeveloped countries. Serum biomarkers could be useful for evaluation of the treatment response and as a complementary means to improve diagnosis. The expression of galectin-9 is altered in cancer tissue, and higher concentrations are found in the serum of cancer patients. The objectives of this study were (a) to determine the serum galectin-9 concentration in patients with intraepithelial lesions and CC, (b) to determine if the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
3
2
0
Order By: Relevance
“…However, a recent study by Beyer et al, concluded that the presence of galectin-9 could be a prognosis marker for cervical cancer. 5 Contradicting this, a previous study reported that the expression of galectin-9 in the tumor cell represented a beneficial response toward the given therapies, 3 which slightly delivered a similar message to this particular study by Reyes-Vallejo et al 4 Hopefully, there will be a clear finding regarding the expression or the concentration of galectin-9 together with other galectin family proteins which may play significant roles in cancer development and prognosis. Therefore, a question worth asking is if there is any correlation to human papillomavirus (HPV) infection affecting the expression of galectin-9 or other galectin family proteins in the cells?…”
Section: Dear Editorsupporting
confidence: 56%
See 2 more Smart Citations
“…However, a recent study by Beyer et al, concluded that the presence of galectin-9 could be a prognosis marker for cervical cancer. 5 Contradicting this, a previous study reported that the expression of galectin-9 in the tumor cell represented a beneficial response toward the given therapies, 3 which slightly delivered a similar message to this particular study by Reyes-Vallejo et al 4 Hopefully, there will be a clear finding regarding the expression or the concentration of galectin-9 together with other galectin family proteins which may play significant roles in cancer development and prognosis. Therefore, a question worth asking is if there is any correlation to human papillomavirus (HPV) infection affecting the expression of galectin-9 or other galectin family proteins in the cells?…”
Section: Dear Editorsupporting
confidence: 56%
“…However, a recent study by Beyer et al, concluded that the presence of galectin-9 could be a prognosis marker for cervical cancer. 5 Contradicting this, a previous study reported that the expression of galectin-9 in the tumor cell represented a beneficial response toward the given therapies, 3 which slightly delivered a similar message to this particular study by Reyes-Vallejo et al 4 …”
Section: Dear Editorsupporting
confidence: 52%
See 1 more Smart Citation
“…They state the importance of detecting other galectins, in respect that we have considered to evaluate serum galectin-9 as a potential biomarker for cervical cancer because this protein plays an important role as an immunomodulator, so it could be related with the immune status of the patients and the progression of the disease. 1 The study of other serum galectins such as galectin-1, galectin-3 and galectin-8 in cervical cancer would certainly generate important information and complement the results obtained in this study.…”
Section: Dear Editorsupporting
confidence: 53%
“…An elevated concentration of sGal-9 was detected in the serum of patients with nasopharyngeal carcinoma in comparison with healthy subjects [ 37 ]. Reyes Vallejo et al, suggested that serum sGal-9 may participate in the progression of cervical cancer and may be a useful prognostic biomarker [ 38 ]. The accumulation of sGal-9 in the PF in our cohort of EMS patients highlights the important role of the soluble form of this lectin in the local peritoneal cavity environment.…”
Section: Discussionmentioning
confidence: 99%